The identity of the cyprinid fishes Rasbora dusonensis and R. tornieri (Teleostei: Cyprinidae) - Ng, Heok Hee; Kottelat, Maurice (Zootaxa, 2013)
Rasbora dusonensis, R. tornieri and R. myersi are valid species. Rasbora dusonensis sensu Brittan (1954) is R. tornieri and R. dusonensis sensu Kottelat (1991) is R. myersi. Both R. dusonensis and R. tornieri are members of the R. argyrotaenia group and can be distinguished from congeners in having a broad, dark, sharply-defined midlateral stripe on body extending from opercle to caudal-fin base and separated from the dark dorsum by a highly contrasting light longitudinal area; 12–14 predorsal scales; the dorsohypural distance equal to or slightly less than the distance between the dorsal-fin origin and the posterior orbital margin and 14 circumpeduncular scale rows. The two species differ from each other by the color and color pattern on the caudal fin, and caudal peduncle depth.